Understanding Purposeful Leadership in Entrepreneurial Contexts: A Bibliometric Analysis - Zaharuddin, Zaharuddin; Wahyuningsih, Sri; Sutarman, Asep; Hikam, Ihsan Nuril (Aptisi Transactions On Technopreneurship (ATT), 2024)
Leadership styles have evolved significantly in response to dynamic business environments and global challenges. Purposeful leadership, in particular, has gained attention for its potential to address these challenges by fostering innovation and ethical decision-making. The aim of this research is to identify and visualize publications on “Purposeful Leadership” within business organizations. This study uses the Dimensions database to collect relevant publications, which are then analyzed and visualized using VOSviewer. The bibliometric analysis includes various visualizations such as country-coupled, organization-coupled, source (journal)-coupled, authors-coupled, document-coupled, and keyword co-occurrence, focusing on articles published from 2014 to 2023. The results show that the USA ranks highest in terms of country-coupled bibliographic terms, with Maharishi International University (USA) leading in organization-coupled terms. The journal with the most citations is identified, while the most frequently cited documents and prolific authors are highlighted. The keyword “leadership” is the most frequently used, while “purposeful leadership” is still emerging, indicating substantial opportunities for future research. The growing interest in purposeful leadership, particularly in the USA, highlights the need for further exploration of this concept, especially in relation to other variables in management and business contexts. The findings emphasize the importance of developing integrative techniques to mobilize collective energy to address significant global challenges like climate change and social injustice. Purposeful leadership offers a solution to these needs, focusing on the role of leaders in articulating and addressing major problems in a focused and inclusive manner. This study underscores the necessity for more comprehensive research to fully understand the impact and potential applications of purposeful leadership in various organizational settings, paving the way for enhanced organizational performance and sustainability.